2018
DOI: 10.3389/fncel.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Contributes to Secondary Brain Injury Through a p38/Drosha Signaling Pathway After Traumatic Brain Injury in Rats

Abstract: Leucine-rich repeat kinase 2 (LRRK2) is widely expressed in the brain and exerts neurotoxicity in Parkinson’s disease. The p38/Drosha signaling activation has been reported to increase cell death under stress. This study was designed to investigate the potential role and mechanism of LRRK2 in secondary brain injury after traumatic brain injury (TBI). A total of 130 male Sprague-Dawley rats were examined using a weight-drop model of TBI. The rats received the specific LRRK2 inhibitor PF-06447475 or LRRK2 pDNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…Western blotting was performed as previously described (Rui et al, 2018). Briefly, proteins were extracted from the peri-injury cortex tissue by homogenization in RIPA buffer (Beyotime, China).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as previously described (Rui et al, 2018). Briefly, proteins were extracted from the peri-injury cortex tissue by homogenization in RIPA buffer (Beyotime, China).…”
Section: Methodsmentioning
confidence: 99%
“…observe overexpression efficiency and conducted the next experiment 24,30,31 . The degree of brain damage and the levels of autophagy and apoptosis were then reassessed.…”
Section: Discussionmentioning
confidence: 99%
“…At 24 h after TBI in experiment II, the degree of nerve injury was evaluated by using the Garcia test 24 (total score of 21), which includes spontaneous activity, body proprioception, response to vibrissae touch, symmetry of limb movement, lateral turning, forelimb outstretching, and climbing ability. Each part of the test was scored from 0 to 3.…”
Section: Neurological Scorementioning
confidence: 99%
“…In immune cells, various pathological stimuli increase LRRK2 level, but the molecular mechanism of LRRK2 induction remains largely unexplored. A recent study showed that LRRK2 level increased in neurons and microglia after weight drop brain injury in rats 47 , but the precise mechanism and the physiological significance of the increase have remained unclear. Here, we show that neurons robustly increase LRRK2 expression in response to injury and such increase was also detected in postmortem brains of CTE patients.…”
Section: Discussionmentioning
confidence: 99%